A multi-element doped porous carbon and a preparation method thereof
Patent Information
- Application Number
- CN202610616105.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-07
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-05-07
AI Technical Summary
氧化石墨烯与酚醛树脂相容性差,导致氧化石墨烯片层团聚、树脂包覆不充分,复合材料碳化后孔道结构杂乱,导电网络不连续,降低超级电容多孔碳的比表面积利用率、离子传输效率与电化学性能。
By in-situ composite of modified graphene oxide and phenolic resin, mercaptoethylamine is introduced to graft mercapto active sites, and 4-(allyloxy)-2-fluorobenzylamine is grafted through a thiol-ene click reaction initiated by ultraviolet light to enhance interfacial compatibility and form a continuous conductive network. Furthermore, heteroatom doping is achieved by constructing multi-level channels through carbonization and activation.
This improved the specific surface area and electrochemical performance of porous carbon, formed highly conductive and abundant pseudocapacitive active sites, and enhanced the electrochemical performance of supercapacitors.
Smart Images

Figure CN122276716B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of porous carbon materials, and in particular to a multi-element doped porous carbon and its preparation method. Background Technology
[0002] Currently, commercially available electric vehicles generally suffer from drawbacks such as long charging times, short driving ranges, and short lifespans. These drawbacks are often addressed by replacing conventional batteries with supercapacitors, which offer high power density, large specific capacitance, and high cycle life. Based on different energy storage mechanisms, supercapacitors can be classified into double-layer capacitors, regular capacitors, and hybrid types. Regular capacitors, due to their transition metal electrode materials, undergo a series of redox reactions during energy storage, resulting in poor cycle stability and long charging times. Double-layer capacitors, on the other hand, use carbon materials as electrode materials, primarily porous carbon.
[0003] Patent CN106115693B discloses a composite phenolic resin-based porous carbon and its preparation method, as well as a supercapacitor. This patent involves in-situ composite of graphene oxide and nitrogen-doped phenolic resin. During curing, the phenolic resin adheres to the graphene oxide sheets, and the barrier effect of the graphene oxide facilitates the formation of mesopores, thereby increasing the mesoporosity of the supercapacitor carbon. Carbonization and alkali activation then yield porous carbon with a large specific surface area. Graphene forms a large conductive network within the porous carbon, while nitrogen doping achieves higher specific capacitance. The prepared porous carbon exhibits low internal resistance, resulting in high electrochemical performance, making it an ideal electrode material for supercapacitors. However, the poor compatibility between graphene oxide and phenolic resin leads to graphene oxide sheet agglomeration and insufficient resin coating. Ultimately, this results in a disordered pore structure and discontinuous conductive network after carbonization and activation of the composite material, significantly reducing the specific surface area utilization, ion transport efficiency, and electrochemical performance of the supercapacitor porous carbon. Summary of the Invention
[0004] This invention provides a multi-element doped porous carbon and its preparation method, which can solve the problems in the prior art where poor compatibility between graphene oxide and phenolic resin leads to graphene oxide sheet aggregation and insufficient resin coating, ultimately resulting in disordered pore structure and discontinuous conductive network after carbonization and activation of the composite material, which significantly reduces the specific surface area utilization, ion transport efficiency and electrochemical performance of porous carbon in supercapacitors.
[0005] The objective of this invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a method for preparing multi-element doped porous carbon, comprising the following steps: S1. Phenol, 4-(2-epoxyethylene methoxy)phenol, formaldehyde aqueous solution and catalyst are mixed to obtain a mixed solution; S2. The modified graphene oxide is sonicated in anhydrous ethanol to obtain a modified graphene oxide solution. S3. Add the modified graphene oxide solution to the mixture, heat to react, then add the curing agent, stir, after the reaction is complete, dehydrate, dry, grind, and cure to obtain modified graphene oxide / phenolic resin. S4. Carbonize the modified graphene oxide / phenolic resin to obtain a carbonized material. S5. Activate the carbonized material to obtain multi-element doped porous carbon.
[0006] Further, in step S1, the ratio of phenol, 4-(2-epoxyethylenemethoxy)phenol, formaldehyde aqueous solution, and catalyst is 94g:13-20g:110-150mL:1-4g; the mass percentage concentration of the formaldehyde aqueous solution is 40%.
[0007] Furthermore, in step S1, the catalyst is triethylamine.
[0008] Further, in step S2, the method for preparing the modified graphene oxide is as follows: S21. Add graphene oxide to anhydrous ethanol and sonicate for 20-30 min. Add mercaptoethylamine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide. Heat the mixture to a slightly refluxed state under stirring and react for 0.5-2 h. Filter, wash, and dry to obtain mercapto-modified graphene oxide. S22. Thiol-modified graphene oxide was added to ethyl acetate and sonicated for 20-30 min. Then, 4-(allyloxy)-2-fluorobenzylamine and benzoin dimethyl ether were added. The mixture was then irradiated under ultraviolet light, washed, and dried to obtain modified graphene oxide.
[0009] Further, in step S21, the ratio of graphene oxide, anhydrous ethanol, mercaptoethylamine, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 3g:1000mL:1.2-3g:0.6-1.5g.
[0010] Further, in step S22, the ratio of the amount of mercapto-modified graphene oxide, ethyl acetate, 4-(allyloxy)-2-fluorobenzylamine, and benzoin dimethyl ether is 3g:500mL:0.2~0.5g:0.01~0.05g.
[0011] Furthermore, in step S22, the wavelength of the ultraviolet light irradiation is 365 nm, and the ultraviolet light intensity is 20–100 mW / cm². 2 The time is 5 to 30 minutes.
[0012] Furthermore, in step S2, the concentration of the modified graphene oxide solution is 2-4 mg / mL.
[0013] Further, in step S3, the ratio of the modified graphene oxide solution, the mixture, and the curing agent is 80-100 mL: 100 mL: 3-10 g.
[0014] Furthermore, in step S3, the heating reaction is carried out at a temperature of 70–80°C for 1–2 hours.
[0015] Furthermore, in step S3, the curing agent is hexamethylenetetramine.
[0016] Furthermore, in step S4, the carbonization temperature is 600–1200°C; the carbonization time is 1–5 hours; and the protective gas used in the carbonization process is nitrogen or argon.
[0017] Further, in step S5, the specific steps of activation are as follows: The carbonized material and potassium hydroxide were dispersed in a 50wt% ethanol aqueous solution, dried, and then added to an activation furnace. Under a nitrogen atmosphere, the mixture was reacted at 600-800℃ for 0.5-2h, cooled to room temperature, washed, and dried to obtain multi-element doped porous carbon.
[0018] Furthermore, the ratio of the carbonized material, potassium hydroxide, and ethanol aqueous solution is 10g:10-40g:200-500mL.
[0019] Secondly, the present invention provides a multi-element doped porous carbon, which is prepared by the preparation method of multi-element doped porous carbon described in any one of the above contents.
[0020] The beneficial effects of this invention are: 1. In step S1 of this invention, phenol, 4-(2-epoxyethylenemethoxy)phenol, formaldehyde aqueous solution, and catalyst are mixed to obtain a mixed solution. By introducing phenolic monomers containing epoxy groups, epoxy active groups are grafted onto the phenolic resin prepolymer, providing sites for subsequent interfacial covalent bonding with modified graphene oxide and increasing the resin crosslinking density. In step S2, modified graphene oxide is ultrasonically dispersed to form a solution. Ultrasonic action is used to achieve uniform dispersion of modified graphene oxide sheets, avoiding agglomeration. At the same time, the active functional groups carried by the modified graphene oxide can enhance the compatibility with the resin. In step S3, the modified graphene oxide solution is reacted with the mixed solution and then cured and post-treated to obtain modified graphene oxide / phenolic resin, realizing in-situ replication of graphene oxide and phenolic resin. In step S4, the modified graphene oxide / phenolic resin is carbonized, transforming the resin matrix into a porous carbon framework. Simultaneously, the graphene oxide is reduced to reduced graphene oxide and a continuous conductive network is constructed within the carbon framework, achieving initial doping and fixation of heteroatoms. Step S5 activates the carbonized material by etching to construct multi-level channels within the carbon framework, significantly increasing the specific surface area of the material and further exposing the active sites of the doped heteroatoms. Ultimately, a multi-element doped porous carbon with high conductivity, high specific surface area, and abundant pseudocapacitive active sites is obtained.
[0021] 2. This invention creatively incorporates modified graphene oxide into the raw materials. First, mercaptoethylamine is grafted to introduce mercaptoactive sites. Then, 4-(allyloxy)-2-fluorobenzylamine is grafted using a UV-induced thiol-ene click reaction while retaining the amino functional group. When combined with phenolic resin, the amino groups on the surface of the modified graphene oxide can covalently react with the epoxy groups carried by the resin, significantly improving the interfacial compatibility between graphene oxide and phenolic resin and preventing sheet aggregation. After carbonization, the reduced graphene oxide constructs a continuous conductive network in the carbon matrix, reducing the internal resistance of the electrode. At the same time, the introduced heteroatoms such as N, S, and F achieve multi-element synergistic doping. After activation, the heteroatom active sites can be further exposed and the pore structure of the carbon material can be regulated, which helps to increase the specific surface area of the multi-element doped porous carbon, thereby improving the electrochemical performance. Attached Figure Description
[0022] Figure 1 This is a scanning electron microscope image of the porous carbon prepared in Example 1 of the present invention. Detailed Implementation
[0023] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below.
[0024] The objective of this invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a method for preparing multi-element doped porous carbon, comprising the following steps: S1. Phenol, 4-(2-epoxyethylene methoxy)phenol, formaldehyde aqueous solution and catalyst are mixed to obtain a mixed solution; Under the action of a catalyst, formaldehyde molecules in the formaldehyde aqueous solution first undergo nucleophilic addition reactions with the phenolic hydroxyl groups of phenol and 4-(2-epoxyethylene methoxy)phenol to generate hydroxymethylphenol intermediates. Subsequently, hydroxymethylphenol intermediates undergo condensation reactions with each other and with unreacted phenol and 4-(2-epoxyethylene methoxy)phenol, removing water molecules to form oligomers linked by methylene bonds. At the same time, the epoxy groups carried by the 4-(2-epoxyethylene methoxy)phenol molecules are retained in the phenolic resin prepolymer molecular chain as active functional groups, providing sites for subsequent interfacial covalent reactions with amino and mercapto groups on the modified graphene oxide surface.
[0025] S2. The modified graphene oxide is sonicated in anhydrous ethanol to obtain a modified graphene oxide solution. By utilizing the cavitation effect generated by ultrasonic vibration, the van der Waals forces between the modified graphene oxide sheets are broken, allowing them to be uniformly dispersed in deionized water to form a stable dispersion.
[0026] S3. Add the modified graphene oxide solution to the mixture, heat to react, then add the curing agent, stir, after the reaction is complete, dehydrate, dry, grind, and cure to obtain modified graphene oxide / phenolic resin. Under heating conditions, the amino-active functional groups on the surface of modified graphene oxide react with the epoxy groups carried by 4-(2-epoxyethylene methoxy)phenol in the phenolic resin prepolymer, achieving a tight bond between the modified graphene oxide and the resin prepolymer and preventing sheet aggregation. After the addition of a curing agent, the molecular chains of the phenolic resin prepolymer undergo further cross-linking reactions to form a three-dimensional network structure, which uniformly anchors the modified graphene oxide sheets in the resin matrix. Subsequent dehydration, drying, and grinding operations remove the solvent and small molecule byproducts from the system, resulting in a structurally stable modified graphene oxide / phenolic resin composite material.
[0027] S4. Carbonize the modified graphene oxide / phenolic resin to obtain a carbonized material. The modified graphene oxide / phenolic resin is carbonized to transform the resin matrix into a porous carbon framework. Simultaneously, the graphene oxide is reduced to reduced graphene oxide and a continuous conductive network is constructed in the carbon framework, while the initial doping and fixation of heteroatoms are achieved.
[0028] S5. Activate the carbonized material to obtain multi-element doped porous carbon.
[0029] By activating the carbonized material and constructing multi-level channels in the carbon framework through etching, the specific surface area of the material is greatly increased. At the same time, the active sites of the doped heteroatoms are further exposed, and finally, a multi-element doped porous carbon with high conductivity, high specific surface area and abundant pseudocapacitive active sites is obtained.
[0030] In some embodiments, in step S1, the ratio of phenol, 4-(2-epoxyethylenemethoxy)phenol, formaldehyde aqueous solution, and catalyst is 94g:13-20g:110-150mL:1-4g; and the mass percentage concentration of the formaldehyde aqueous solution is 40%. The molar ratio of phenol to formaldehyde at this formulation is within the optimal range for the preparation of phenolic resin prepolymers, ensuring that the prepolymer has a suitable molecular weight and reactivity, and avoiding excessive or insufficient crosslinking of the resin. The dosage of 13-20g of 4-(2-epoxyethylenemethoxy)phenol can introduce an appropriate amount of epoxy active groups into the resin molecular chain, providing sufficient sites for subsequent covalent bonding with the amino and mercapto groups of modified graphene oxide, while preventing the resin prepolymer from agglomerating due to excessive epoxy groups. The addition of 1-4g of catalyst can precisely control the addition-condensation reaction rate, ensuring that the reaction is mild and controllable, and reducing the generation of by-products. The final mixture has good dispersibility and high stability. After being combined with the modified graphene oxide solution, it can significantly improve the interfacial bonding force of the composite material, laying the structural foundation for the subsequent carbonization and activation to prepare high specific capacitance porous carbon.
[0031] A 40% formaldehyde aqueous solution can ensure that the reactivity of formaldehyde and phenolic monomers is within the optimal range. This provides sufficient reaction raw materials for the preparation of phenolic resin prepolymers, while avoiding excessive self-polymerization of formaldehyde or excessive cross-linking of resin due to excessive concentration. It also takes into account the stability of raw materials and the controllability of the process.
[0032] In some embodiments, the catalyst in step S1 is triethylamine. As a basic catalyst, triethylamine can efficiently activate the ortho- and para-active hydrogens of the phenolic hydroxyl groups of phenol and 4-(2-epoxyethylenemethoxy)phenol, accelerating their nucleophilic addition reaction with formaldehyde and shortening the prepolymer preparation time. At the same time, the basicity of triethylamine is mild, which will not cause excessive cross-linking in the reaction system. It can precisely control the molecular weight and molecular chain structure of the phenolic resin prepolymer, ensuring that the prepolymer has appropriate reactivity and solubility. In addition, triethylamine is easily volatilized through the subsequent heating process, and will not leave impurities in the resin matrix, avoiding negative impacts on the subsequent carbonization, activation process and the electrochemical performance of the final porous carbon.
[0033] Graphene oxide, as a precursor for carbon materials and a reinforcing phase in composite materials, possesses a layered structure, abundant oxygen-containing functional groups, and a large specific surface area. Its layers can serve as the framework for constructing conductive networks. After carbonization, it transforms into reduced graphene oxide, which can improve the conductivity and electron transport efficiency of the carbon matrix. The carboxyl and hydroxyl groups on its surface can serve as active sites for subsequent chemical modification, providing a basis for introducing heteroatoms or functional groups. However, graphene oxide also has significant drawbacks. The strong van der Waals forces between its layers easily lead to irreversible aggregation, resulting in poor compatibility and difficulty in uniform dispersion when directly composited with phenolic resins. Furthermore, containing only carbon and oxygen, it cannot directly achieve multi-element synergistic doping. Additionally, the unmodified graphene oxide and the resin matrix are only physically bonded, with weak interfacial forces, leading to decreased structural stability after carbonization of the composite material, ultimately affecting the specific surface area and electrochemical performance of multi-element doped porous carbon. Therefore, this invention further improves graphene oxide.
[0034] In some embodiments, the method for preparing the modified graphene oxide in step S2 is as follows: S21. Add graphene oxide to anhydrous ethanol and sonicate for 20-30 min. Add mercaptoethylamine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide. Heat the mixture to a slightly refluxed state under stirring and react for 0.5-2 h. Filter, wash, and dry to obtain mercapto-modified graphene oxide. In the above reaction steps, ultrasonic vibration first breaks the van der Waals forces between graphene oxide sheets in an anhydrous ethanol dispersion system, achieving uniform dispersion. Subsequently, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide acts as a dehydration condensation agent, activating oxygen-containing functional groups such as carboxyl groups on the graphene oxide surface, promoting a dehydration condensation reaction with the amino groups in the mercaptoethylamine molecule, and covalently grafting thiol groups onto the graphene oxide surface via amide bonds. The micro-reflux reaction conditions accelerate the reaction process and ensure the uniformity and stability of thiol grafting. Finally, unreacted raw materials and byproducts are removed by filtration, washing, and drying to obtain thiolized graphene oxide. This process introduces thiol groups through covalent grafting rather than physical adsorption, which not only improves the dispersibility of graphene oxide in organic solvents but also provides active sites for subsequent thiol-ene UV click reactions, while avoiding the loss of thiol groups during subsequent composite processes, laying the structural foundation for multi-element doping.
[0035] S22. Thiol-modified graphene oxide was added to ethyl acetate and sonicated for 20-30 min. Then, 4-(allyloxy)-2-fluorobenzylamine and benzoin dimethyl ether were added. The mixture was then irradiated under ultraviolet light, washed, and dried to obtain modified graphene oxide.
[0036] In an ethyl acetate dispersion system, ultrasonic vibration can break up the local agglomeration of thiolized graphene oxide, making it uniformly dispersed. Subsequently, benzoin dimethyl ether, as a UV photoinitiator, decomposes under UV irradiation to generate free radicals, triggering a thiol-alkene click reaction between the thiol (-SH) groups on the surface of thiolized graphene oxide and the carbon-carbon double bond (C=C) in the 4-(allyloxy)-2-fluorobenzylamine molecule. This allows nitrogen- and fluorine-containing functional groups to be grafted onto the surface of graphene oxide through covalent bonds. After washing and drying to remove unreacted monomers and initiators, modified graphene oxide containing multiple elements such as N, S, and F is obtained. This process, involving thiol-ene click reactions, is characterized by high efficiency, strong selectivity, and mild reaction conditions. It enables precise grafting of functional groups, significantly improving modification efficiency. The grafted nitrogen- and fluorine-containing functional groups not only further enhance the dispersion stability of graphene oxide in organic solvents but also provide N and F heteroatom doping sources for subsequent carbonization processes. These doping groups, along with the S element introduced by the thiol group, form a multi-element synergistic doping effect. Meanwhile, the retained amino groups can undergo covalent reactions with the epoxy groups in phenolic resins, enhancing interfacial bonding. This lays a crucial structural foundation for the preparation of multi-element doped porous carbon with high specific capacitance.
[0037] In some embodiments, in step S21, the ratio of graphene oxide, anhydrous ethanol, mercaptoethylamine, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) is 3g:1000mL:1.2-3g:0.6-1.5g. 1000 mL of anhydrous ethanol can fully disperse 3 g of graphene oxide, avoiding the obscuring of active sites caused by sheet aggregation and providing a uniform reaction environment for the grafting reaction. The gradient dosage of 1.2–3 g of mercaptoethylamine can flexibly control the mercapto grafting density and form an optimal ratio of 1:0.5 with EDC. EDC can efficiently activate the carboxyl groups on the surface of graphene oxide, promoting their dehydration condensation reaction with the amino groups of mercaptoethylamine. This ensures a stable increase in the mercapto grafting rate and avoids the increase in side reactions and post-processing burden caused by excessive raw materials. The mercapto-modified graphene oxide prepared under this ratio has a uniform mercapto group distribution and good dispersion stability, which can provide sufficient active sites for the subsequent thiol-ene click reaction and lay a reliable structural foundation for the realization of multi-element synergistic doping.
[0038] In some embodiments, in step S22, the ratio of the amount of mercapto-modified graphene oxide, ethyl acetate, 4-(allyloxy)-2-fluorobenzylamine, and benzoin dimethyl ether is 3g:500mL:0.2-0.5g:0.01-0.05g. 500 mL of ethyl acetate can achieve uniform dispersion of 3 g of mercapto-modified graphene oxide, avoiding uneven local reactions caused by sheet aggregation; the gradient dosage of 0.2–0.5 g of fluorine- and nitrogen-containing monomers can precisely match the mercapto groups on the surface of mercapto-modified graphene oxide, ensuring the full progress of the thiol-ene click reaction, and controlling the grafting density of N and F heteroatoms by adjusting the monomer dosage, avoiding side reactions caused by excessive monomers; 0.01–0.05 g of benzoin dimethyl ether, as a UV initiator, with an appropriate dosage to the monomer ratio, can efficiently trigger free radical reactions, ensuring grafting efficiency while reducing initiator residue; the modified graphene oxide prepared under this ratio has a uniform heteroatom distribution and excellent interfacial compatibility with phenolic resin, providing a key structural guarantee for the subsequent carbonization preparation of high specific capacitance multi-element doped porous carbon.
[0039] In some embodiments, in step S22, the wavelength of the ultraviolet light irradiation is 365 nm, and the ultraviolet light intensity is 20–100 mW / cm². 2 The time is 5–30 min. 365 nm is the optimal absorption wavelength for the benzoin dimethyl ether initiator, which can efficiently excite the initiator to decompose and generate free radicals, rapidly triggering the covalent bonding of thiol groups on the surface of thiolized graphene oxide with the double bonds of fluorine- and nitrogen-containing monomers; 20–100 mW / cm². 2 The gradient ultraviolet light intensity and gradient duration of 5–30 min can be flexibly matched to the reaction requirements under different monomer dosages. Low ultraviolet light intensity for short time is suitable for systems with low monomer dosage, avoiding sheet aggregation caused by over-reaction. High ultraviolet light intensity for long time can promote the reaction of systems with high monomer dosage to proceed fully and increase the heteroatom grafting density. The reaction conditions under these irradiation parameters are mild and controllable, without the need for high temperature and high pressure, and will not damage the graphene oxide sheet structure. The resulting modified graphene oxide has a uniform heteroatom distribution, which provides a reliable guarantee for the high specific capacitance performance of subsequent multi-element synergistic doping of porous carbon.
[0040] In some embodiments, in step S2, the concentration of the modified graphene oxide solution is 2–4 mg / mL. This concentration range ensures that the modified graphene oxide is uniformly dispersed in deionized water. It avoids excessively high concentrations that could lead to sheet aggregation, decreased dispersion stability, and difficulty in uniform mixing with phenolic resin; and also avoids excessively low concentrations that would result in insufficient graphene oxide content per unit volume of dispersion, preventing the formation of a continuous conductive network during subsequent composite with phenolic resin. Simultaneously, the 2–4 mg / mL concentration matches the addition ratio of the mixture in step S3, allowing for precise control of the graphene oxide doping amount in the composite material. This avoids excessive doping causing carbon framework defects, or insufficient doping failing to leverage the synergistic doping of heteroatoms and the gain effect of the conductive network, thus laying a uniform structural foundation for subsequent carbonization and activation to prepare high-specific-capacitance multi-element doped porous carbon.
[0041] In some embodiments, in step S3, the ratio of the modified graphene oxide solution, the mixture, and the curing agent is 80-100 mL: 100 mL: 3-10 g. The ratio of 80–100 mL of modified graphene oxide solution to 100 mL of mixed solution ensures uniform distribution of the modified graphene oxide sheets in the phenolic resin prepolymer. This avoids both excessively high graphene oxide content leading to hindered cross-linking of the resin matrix and increased carbon skeleton brittleness, and insufficient content preventing the formation of a continuous conductive network. The 3–10 g curing agent dosage is compatible with the reactivity of the resin prepolymer in the system, promoting full cross-linking of the resin molecular chains and firmly anchoring the modified graphene oxide sheets in the three-dimensional network structure, thus improving the interfacial bonding and structural stability of the composite material. This ratio can flexibly match the composite requirements of different concentrations of modified graphene oxide solution, providing a reliable guarantee for the formation of pore structures and uniform doping of heteroatoms during subsequent carbonization and activation processes, ultimately achieving a steady improvement in the specific capacitance performance of multi-element doped porous carbon.
[0042] In some embodiments, in step S3, the heating reaction temperature is 70–80°C, and the time is 1–2 hours. This temperature range is within the suitable reaction temperature range for phenolic resin prepolymers, which can efficiently activate the ring-opening addition reaction between the amino and mercapto groups on the surface of modified graphene oxide and the epoxy groups in the resin prepolymer, while avoiding structural defects caused by premature resin curing or excessive volatilization of small molecules due to high temperature. The reaction time of 1–2 hours provides sufficient time for the full formation of interfacial covalent bonds, ensuring both the tight bonding between the modified graphene oxide sheets and the resin matrix and preventing excessive cross-linking of the system due to excessive reaction time. Finally, the composite material obtained under these conditions has uniform dispersion and strong interfacial bonding, laying a stable structural foundation for the construction of conductive networks and uniform doping of heteroatoms during subsequent curing and carbonization processes.
[0043] In some embodiments, in step S3, the curing agent is hexamethylenetetramine. Hexamethylenetetramine, as a dedicated curing agent for phenolic resins, decomposes under heating conditions to produce formaldehyde and amines. This provides sufficient active sites for the crosslinking reaction of the phenolic resin prepolymer, promoting the rapid formation of a dense three-dimensional network structure of the resin molecular chains. Furthermore, it can synergistically enhance the interfacial bonding between the graphene oxide sheets and the resin matrix through the amine groups and the residual active functional groups on the surface of the modified graphene oxide. Simultaneously, the curing reaction of this curing agent is mild and controllable, preventing the formation of pores or cracks in the composite material due to localized exothermic reactions. The resulting modified graphene oxide / phenolic resin structure is uniform and dense, providing a stable precursor basis for the formation of a porous carbon skeleton and the uniform doping of heteroatoms during subsequent carbonization.
[0044] In some embodiments, in step S4, the carbonization temperature is 600–1200°C; the carbonization time is 1–5 hours; and the protective gas during the carbonization process is nitrogen or argon. The gradient temperature range of 600–1200℃ can flexibly match different heteroatom doping requirements. The low-temperature range (600–800℃) can retain more N, S, and F heteroatoms and form a rich mesoporous structure, while the high-temperature range (800–1200℃) can improve the graphitization degree and conductivity of the carbon framework. The carbonization time of 1–5 hours provides sufficient time for resin pyrolysis, aromatization, and pore formation, avoiding incomplete carbonization due to too short a time or pore collapse due to too long a time. The inert atmosphere of nitrogen or argon can effectively isolate oxygen, prevent high-temperature oxidation and ablation of carbon materials, and suppress excessive volatilization of heteroatoms, ensuring the efficiency of multi-element synergistic doping. The carbonized material prepared under these process parameters has high conductivity, rich hierarchical pores, and uniform heteroatom distribution, providing a high-quality precursor for subsequent activation preparation of high specific capacitance multi-element doped porous carbon.
[0045] In some embodiments, the activation step in step S5 is as follows: The carbonized material and potassium hydroxide were dispersed in a 50wt% ethanol aqueous solution, dried, and then added to an activation furnace. Under a nitrogen atmosphere, the mixture was reacted at 600-800℃ for 0.5-2h, cooled to room temperature, washed, and dried to obtain multi-element doped porous carbon.
[0046] A 50wt% ethanol-water solution can achieve uniform mixing of carbon materials and potassium hydroxide, avoiding uneven distribution of activators caused by solid-phase mixing and improving the consistency of the activation reaction. As a strong activator, potassium hydroxide can undergo an etching reaction with the carbon skeleton at 600–800℃, creating and expanding pores to form a hierarchical pore structure with good connectivity, significantly increasing the specific surface area of the material. A nitrogen atmosphere can prevent the carbon material from being oxidized and lost at high temperatures, while inhibiting excessive removal of heteroatoms and ensuring stable doping of elements such as N, S, and F. An activation time of 0.5–2 hours can precisely control the pore size and distribution, avoiding insufficient activation leading to fewer pores or over-activation causing the carbon skeleton to collapse. Subsequent washing removes residual alkali, and the final multi-element doped porous carbon has a high specific surface area, a reasonable pore structure, and a uniform heteroatom distribution, which can significantly improve the charge storage and transport efficiency of supercapacitors.
[0047] In some embodiments, the ratio of the carbide material, potassium hydroxide, and ethanol aqueous solution is 10g:10-40g:200-500mL. The 200-500mL 50wt% ethanol aqueous solution ensures uniform dispersion of the carbide material and potassium hydroxide, avoiding localized over-etching or under-activation caused by activator agglomeration during solid-phase mixing. The gradient dosage of 10-40g of potassium hydroxide allows for flexible matching of the carbon skeleton structure of the carbide material; a low ratio can moderately create uniform mesopores, while a high ratio can deeply etch and construct rich hierarchical channels, while simultaneously inhibiting carbon skeleton collapse. The mixed system at this dosage ratio exhibits good stability, and after drying, the activator and carbide material are in sufficient contact. During activation in a nitrogen atmosphere, it can efficiently perform etching, significantly increasing the specific surface area and pore volume of porous carbon, while retaining the synergistic doping effect of heteroatoms such as N, S, and F. The resulting multi-element doped porous carbon possesses excellent charge adsorption and transport capabilities, meeting the high-performance requirements of supercapacitors.
[0048] Secondly, the present invention provides a multi-element doped porous carbon, which is prepared by the preparation method of multi-element doped porous carbon described in any one of the above contents.
[0049] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.
[0050] In this invention, the graphene oxide sheet has a diameter of 12 micrometers, a sheet thickness of 5 nanometers, and an oxygen content of 40 wt%. The 12-micrometer diameter, 5-nanometer thickness, and 40 wt% oxygen content of the graphene oxide can form a continuous conductive network when combined with phenolic resin, providing sufficient active sites for efficient heteroatom grafting, while ensuring interfacial compatibility with the resin. Ultimately, this endows porous carbon with excellent conductivity, pore structure, and pseudocapacitive properties.
[0051] Preparation Example Preparation Example 1 The preparation method of modified graphene oxide is as follows: S21. Add 3g of graphene oxide to 1000mL of anhydrous ethanol and sonicate for 20min. Add 1.2g of mercaptoethylamine and 0.6g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide. Heat the mixture to a slightly refluxed state under stirring and react for 0.5h. Filter, wash, and dry to obtain mercapto-modified graphene oxide. S22. Add 3g of mercapto-modified graphene oxide to 500mL of ethyl acetate and sonicate for 20min. Then add 0.2g of 4-(allyloxy)-2-fluoroaniline and 0.01g of benzoin dimethyl ether, and irradiate under ultraviolet light at a wavelength of 365nm and an intensity of 20mW / cm². 2 The process takes 5 minutes, followed by washing and drying to obtain modified graphene oxide.
[0052] Preparation Example 2 The preparation method of modified graphene oxide is as follows: S21. Add 3g of graphene oxide to 1000mL of anhydrous ethanol and sonicate for 25min. Add 2.1g of mercaptoethylamine and 1.05g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide. Heat the mixture to a slightly refluxed state under stirring and react for 1.2h. Filter, wash, and dry to obtain mercapto-modified graphene oxide. S22. Add 3g of mercapto-modified graphene oxide to 500mL of ethyl acetate and sonicate for 25min. Then add 0.35g of 4-(allyloxy)-2-fluoroaniline and 0.03g of benzoin dimethyl ether, and irradiate under ultraviolet light at a wavelength of 365nm and an intensity of 60mW / cm². 2 The time was 18 minutes, followed by washing and drying to obtain modified graphene oxide.
[0053] Preparation Example 3 The preparation method of modified graphene oxide is as follows: S21. Add 3g of graphene oxide to 1000mL of anhydrous ethanol and sonicate for 30min. Add 3g of mercaptoethylamine and 1.5g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide. Heat the mixture to a slightly refluxed state under stirring and react for 2h. Filter, wash, and dry to obtain mercapto-modified graphene oxide. S22. Add 3g of mercapto-modified graphene oxide to 500mL of ethyl acetate and sonicate for 30min. Then add 0.5g of 4-(allyloxy)-2-fluoroaniline and 0.05g of benzoin dimethyl ether, and irradiate under ultraviolet light at a wavelength of 365nm and an intensity of 100mW / cm². 2 The time was 30 minutes, followed by washing and drying to obtain modified graphene oxide.
[0054] Comparison Example Compare with Example 1 The only difference between this comparative example and preparation example 1 is that "4-(allyloxy)-2-fluorobenzylamine" was replaced with an equal amount of "4-(prop-2-en-1-oxy)phenyl]methylamine".
[0055] Compare with Example 2 The only difference between this comparative example and preparation example 1 is that step S22, involving the addition of 4-(allyloxy)-2-fluorobenzylamine, is omitted. The specific steps are as follows: 3g of graphene oxide was added to 1000mL of anhydrous ethanol and sonicated for 20min. Then, 1.2g of mercaptoethylamine and 0.6g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide were added. The mixture was heated to micro-reflux under stirring and reacted for 0.5h. The mixture was then filtered, washed, and dried to obtain mercapto-modified graphene oxide, which is the modified graphene oxide.
[0056] Example Example 1 A method for preparing multi-element doped porous carbon includes the following steps: S1. Mix 94g phenol, 13g 4-(2-epoxyethylene methoxy)phenol, 110mL of formaldehyde aqueous solution with a mass percentage concentration of 40%, and 1g triethylamine to obtain a mixed solution; S2. 0.2g of the modified graphene oxide obtained in Preparation Example 1 was sonicated in 100mL of anhydrous ethanol to obtain a modified graphene oxide solution. S3. Add 80 mL of modified graphene oxide solution to 100 mL of mixed solution, heat at 70 °C for 1 h, then add 3 g of hexamethylenetetramine, stir, after the reaction is complete, dehydrate, dry, grind, and cure at 150 °C for 1 h to obtain modified graphene oxide / phenolic resin. S4. The modified graphene oxide / phenolic resin was carbonized at 600°C for 1 hour under argon atmosphere to obtain the carbonized material. S5. Disperse 10g of carbide material and 10g of potassium hydroxide in 200mL of 50wt% ethanol aqueous solution, dry, then add to an activation furnace, react at 600℃ for 0.5h under nitrogen atmosphere, cool to room temperature, wash, and dry to obtain multi-element doped porous carbon; the scanning electron microscope image of this porous carbon is shown below. Figure 1 As shown, from Figure 1 It can be seen that the porous carbon prepared in this invention was successful, and the particle size was uniform.
[0057] Example 2 A method for preparing multi-element doped porous carbon includes the following steps: S1. Mix 94g phenol, 16.6g 4-(2-epoxyethylene methoxy)phenol, 130mL of 40% formaldehyde aqueous solution, and 2.5g triethylamine to obtain a mixed solution; S2. 0.3g of the modified graphene oxide obtained in Preparation Example 1 was sonicated in 100mL of anhydrous ethanol to obtain a modified graphene oxide solution. S3. Add 90 mL of modified graphene oxide solution to 100 mL of mixed solution, heat at 75 °C for 1.5 h, then add 6 g of hexamethylenetetramine, stir, after the reaction is complete, dehydrate, dry, grind, and cure at 150 °C for 1 h to obtain modified graphene oxide / phenolic resin. S4. The modified graphene oxide / phenolic resin was carbonized at 900°C for 3 hours under argon atmosphere to obtain the carbonized material. S5. Disperse 10g of carbide material and 25g of potassium hydroxide in 350mL of 50wt% ethanol aqueous solution, dry, then add to an activation furnace, react at 700℃ for 1.3h under nitrogen atmosphere, cool to room temperature, wash, and dry to obtain multi-element doped porous carbon.
[0058] Example 3 A method for preparing multi-element doped porous carbon includes the following steps: S1. Mix 94g phenol, 20g 4-(2-epoxyethylene methoxy)phenol, 150mL of formaldehyde aqueous solution with a mass percentage concentration of 40%, and 4g triethylamine to obtain a mixed solution; S2. 0.4g of the modified graphene oxide obtained in Preparation Example 1 was sonicated in 100mL of anhydrous ethanol to obtain a modified graphene oxide solution. S3. Add 100 mL of modified graphene oxide solution to 100 mL of mixed solution, heat at 80 °C for 2 h, then add 6.5 g of hexamethylenetetramine, stir, after the reaction is complete, dehydrate, dry, grind, and cure at 150 °C for 1 h to obtain modified graphene oxide / phenolic resin. S4. The modified graphene oxide / phenolic resin was carbonized at 1200℃ for 5 hours under argon atmosphere to obtain the carbonized material. S5. Disperse 10g of carbide material and 40g of potassium hydroxide in 500mL of 50wt% ethanol aqueous solution, dry, then add to an activation furnace, react at 800℃ for 2h under nitrogen atmosphere, cool to room temperature, wash, and dry to obtain multi-element doped porous carbon.
[0059] Example 4 The only difference between this embodiment and Example 1 is that "the modified graphene oxide obtained in Example 1" is replaced with "the modified graphene oxide obtained in Example 2".
[0060] Example 5 The only difference between this embodiment and Example 1 is that "the modified graphene oxide obtained in Example 1" is replaced with "the modified graphene oxide obtained in Example 3".
[0061] Comparative Example Comparative Example 1 The only difference between this comparative example and Example 1 is that "modified graphene oxide obtained in Preparation Example 1" is replaced with "modified graphene oxide obtained in Control Example 1".
[0062] Comparative Example 2 The only difference between this comparative example and Example 1 is that "modified graphene oxide obtained in Preparation Example 1" is replaced with "modified graphene oxide obtained in Control Example 2".
[0063] Comparative Example 3 The only difference between this comparative example and Example 1 is that "modified graphene oxide obtained in Preparation Example 1" is replaced with "graphene oxide".
[0064] Compare with Example 4 The only difference between this comparative example and Example 1 is that 4-(2-epoxyethylene methoxy)phenol in step S1 is omitted.
[0065] Compare with Example 5 The only difference between this comparative example and Example 1 is that 4-(2-epoxyethylene methoxy)phenol in step S1 is omitted; and "modified graphene oxide obtained in Example 1" is replaced with "graphene oxide".
[0066] Test case Multi-element doped porous carbon, acetylene black, and polytetrafluoroethylene prepared in Examples 1-5 and Comparative Examples 1-5 were added in a mass ratio of 85:10:5, respectively. After mixing and rolling into a thin film, the mixture was stamped into an electrode sheet with a diameter of 1 cm. Using 6 M KOH as the electrolyte, the specific capacitance was tested at a current density of 2 A / g. The test results are shown in Table 1. Table 1
[0067] As can be seen from Table 1, the porous carbon prepared in Examples 1 to 5 of the present invention has higher conductivity than that of Comparative Examples 1 to 5.
[0068] The capacitance value of Comparative Example 1 was 202 F / g, slightly lower than that of Example 1 (211 F / g). This is because although the graphene oxide used contained amino groups, it lacked fluorine atoms. Fluorine atoms have strong electronegativity, and their doping can optimize the electronic structure of carbon materials, enhance the adsorption of electrolyte ions on the carbon matrix, and increase the number of defect sites in carbon materials, providing more active centers for pseudocapacitive reactions. In contrast, the modified monomer of Comparative Example 1 did not contain fluorine, thus resulting in a decrease in specific capacitance performance.
[0069] Comparative Example 2 omitted 4-(allyloxy)-2-fluorobenzylamine and directly used mercapto-modified graphene oxide as the modified graphene oxide. Its specific capacitance was 193 F / g, significantly lower than that of Example 1. This is because omitting the fluorine- and amino-containing monomers leaves only mercapto functional groups on the surface of the modified graphene oxide, lacking covalent bonding sites between amino groups and epoxy groups in the phenolic resin. This results in poor dispersibility of the graphene oxide in the resin matrix, making it prone to aggregation after carbonization and unable to form a continuous conductive network. At the same time, this comparative example can only introduce sulfur and nitrogen doping, lacking the synergistic effect of fluorine, which significantly reduces the number of active sites in the carbon material, ultimately leading to a decrease in specific capacitance.
[0070] Comparative Example 3 directly used unmodified graphene oxide to replace the modified graphene oxide in Example 1, and its specific capacitance was only 180 F / g, which was the worst performing group among the Example and Comparative Example groups. The oxygen-containing functional groups on the surface of unmodified graphene oxide have poor compatibility with phenolic resin, and irreversible agglomeration easily occurs during the composite process. After carbonization, it is impossible to build a uniform conductive path in the carbon matrix, and the charge transfer resistance increases significantly. In addition, unmodified graphene oxide does not have the conditions for heteroatom doping, and the carbon material only relies on its own pore structure to provide double-layer capacitance, lacking the contribution of pseudocapacitance. Therefore, the specific capacitance performance is much lower than that of Example 1, which uses modified graphene oxide.
[0071] Comparative Example 4 omitted 4-(2-epoxyethylene methoxy)phenol in step S1, using only phenol and formaldehyde to synthesize phenolic resin. Its specific capacitance was 198 F / g, lower than that of Example 1. The core function of 4-(2-epoxyethylene methoxy)phenol is to introduce epoxy active groups into the phenolic resin prepolymer. These groups can undergo ring-opening reactions with the amino groups on the surface of modified graphene oxide, achieving covalent bonding between the resin and graphene oxide and improving the interfacial bonding of the composite material. However, the phenolic resin in Comparative Example 4 lacks epoxy groups and is only physically mixed with modified graphene oxide. After carbonization, the carbon skeleton structure is prone to defects, resulting in poor pore connectivity and reduced ion transport efficiency, which in turn leads to a decrease in specific capacitance performance.
[0072] Comparative Example 5 omitted 4-(2-epoxyethylenemethoxy)phenol and used unmodified graphene oxide, resulting in a specific capacitance of only 169 F / g, the lowest among all test groups. This comparative example combined the disadvantages of Comparative Examples 3 and 4: on the one hand, unmodified graphene oxide has poor compatibility with phenolic resin, is prone to agglomeration, and lacks heteroatom doping; on the other hand, phenolic resin lacks epoxy active groups and cannot form covalent bonds with graphene oxide. After carbonization, the carbon matrix structure is loose, the pores collapse severely, and the number of conductive networks and active sites is greatly reduced, thus achieving the lowest specific capacitance performance.
[0073] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.
Claims
1. A method for preparing multi-element doped porous carbon, characterized in that, Includes the following steps: S1. Phenol, 4-(2-epoxyethylene methoxy)phenol, formaldehyde aqueous solution and catalyst are mixed to obtain a mixed solution; S2. The modified graphene oxide is sonicated in anhydrous ethanol to obtain a modified graphene oxide solution; the preparation method of the modified graphene oxide is as follows: S21. Add graphene oxide to anhydrous ethanol and sonicate for 20-30 min. Add mercaptoethylamine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide. Heat the mixture to a slightly refluxed state under stirring and react for 0.5-2 h. Filter, wash, and dry to obtain mercapto-modified graphene oxide. S22. Thiolized graphene oxide was added to ethyl acetate and sonicated for 20-30 min. Then 4-(allyloxy)-2-fluorobenzylamine and benzoin dimethyl ether were added. The mixture was irradiated under ultraviolet light, washed, and dried to obtain modified graphene oxide. S3. Add the modified graphene oxide solution to the mixture, heat to react, then add the curing agent, stir, after the reaction is complete, dehydrate, dry, grind, and cure to obtain modified graphene oxide / phenolic resin. S4. Carbonize the modified graphene oxide / phenolic resin to obtain a carbonized material. S5. Activate the carbonized material to obtain multi-element doped porous carbon.
2. The method for preparing multi-element doped porous carbon according to claim 1, characterized in that, In step S1, the ratio of phenol, 4-(2-epoxyethylenemethoxy)phenol, formaldehyde aqueous solution, and catalyst is 94g:13-20g:110-150mL:1-4g. The formaldehyde aqueous solution has a mass percentage concentration of 40%. The catalyst is triethylamine.
3. The method for preparing multi-element doped porous carbon according to claim 1, characterized in that, In step S21, the ratio of graphene oxide, anhydrous ethanol, mercaptoethylamine, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 3g:1000mL:1.2-3g:0.6-1.5g.
4. The method for preparing multi-element doped porous carbon according to claim 1, characterized in that, In step S22, the ratio of the amount of mercapto-modified graphene oxide, ethyl acetate, 4-(allyloxy)-2-fluorobenzylamine, and benzoin dimethyl ether is 3g:500mL:0.2-0.5g:0.01-0.05g; The wavelength of the ultraviolet light irradiation is 365 nm, and the ultraviolet light intensity is 20–100 mW / cm². 2 The time is 5 to 30 minutes.
5. The method for preparing multi-element doped porous carbon according to claim 1, characterized in that, In step S2, the concentration of the modified graphene oxide solution is 2-4 mg / mL.
6. The method for preparing multi-element doped porous carbon according to claim 1, characterized in that, In step S3, the ratio of the modified graphene oxide solution, the mixture, and the curing agent is 80-100 mL: 100 mL: 3-10 g. The heating reaction is carried out at a temperature of 70–80°C for 1–2 hours. The curing agent is hexamethylenetetramine.
7. The method for preparing multi-element doped porous carbon according to claim 1, characterized in that, In step S4, the carbonization temperature is 600–1200°C; the carbonization time is 1–5 hours. The protective gas used in the carbonization process is nitrogen or argon.
8. The method for preparing multi-element doped porous carbon according to claim 1, characterized in that, In step S5, the specific activation steps are as follows: The carbide material and potassium hydroxide were dispersed in a 50wt% ethanol aqueous solution, dried, and then added to an activation furnace. Under a nitrogen atmosphere, the reaction was carried out at 600-800℃ for 0.5-2h. After cooling to room temperature, the material was washed and dried to obtain multi-element doped porous carbon. The ratio of the carbonized material, potassium hydroxide, and ethanol aqueous solution is 10g: 10-40g: 200-500mL.
9. A multi-element doped porous carbon, characterized in that, It is prepared by the method for preparing multi-element doped porous carbon according to any one of claims 1-8.
Citation Information
Patent Citations
A composite phenolic resin-based activated carbon and its preparation method, and a supercapacitor.
CN106115693B
Preparation method of phenolic resin-based porous carbon based on modification of graphene
CN107253708A
Modified graphene oxide based on wet chemical modification and preparation method thereof
CN120622476A
